Libraries and financial literacy: perspectives from emerging markets - Špiranec, Sonja; Stokić Simončić, Gordana; Banek Zorica, Mihaela (2012)
The article uses conceptual correlations between information literacy and financial literacy as a basis for arguing that financial literacy services have a place in library settings. The article discusses the general requirements, profile o f services, and various challenges related to the introduction o f financial literacy programmes in public libraries. An intensified interest in financial literacy matters may be assigned to the global financial crisis o f 2007 to 2009. The interdependencies between financial crisis, financial literacy, and the potential of public libraries is illustrated by the example of one South-Eastern European country whose economic transformations and developments reflect the importance of financial literacy.
Projekt MZOS
ENG